2014
DOI: 10.1127/0003-5548/2014/0368
|View full text |Cite
|
Sign up to set email alerts
|

Y-SNP analysis versus Y-Haplogroup Predictor in the Slovak population

Abstract: Human Y-chromosome haplogroups are important markers used mainly in population genetic studies. The haplogroups are defined by several SNPs according to the phylogeny and international nomenclature. The alternative method to estimate the Y-chromosome haplogroups is to predict Y-chromosome haplotypes from a set of Y-STR markers using software for Y-haplogroup prediction. The purpose of this study was to compare the accuracy of three types of Y-haplogroup prediction software and to determine the structure of Slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…4). Athey's algorithm is reported to be relatively efficient for prediction of haplogroups as compared to the other available tools 21 and it has been shown that the use of 17 or more Y-STRs is efficient for the prediction of haplogroups 22,23 . However, caution must be exercised while drawing interpretations based on the haplogroups derived from this algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…4). Athey's algorithm is reported to be relatively efficient for prediction of haplogroups as compared to the other available tools 21 and it has been shown that the use of 17 or more Y-STRs is efficient for the prediction of haplogroups 22,23 . However, caution must be exercised while drawing interpretations based on the haplogroups derived from this algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Another predictor tool[16], was also used for confirmation purposes. These two haplogroup prediction tools have been found to have a validity of 99% and 97%, respectively, in assigning major haplogroups and subclades[17]. Haplotypes that were assigned a haplogroup with a probability <90%, underwent specific Y-SNP genotyping to confirm the haplogroup.…”
Section: Methodsmentioning
confidence: 99%
“…Our approach for determining haplogroup distributions comprised the following steps: (i) extracting the raw haplogroup data (absolute numbers) from each study; (ii) standardizing the nomenclature for each haplogroup [International Society of Genetic Genealogy (2016)]; (iii) merging data from different studies and summing the absolute frequency of each haplogroup for each population/sub-population; and (iv) calculating relative frequencies (%) of each haplogroup for each population/sub-population, using the merged data. Due to the fact that a key study containing Turkish and Kurdish samples from Central Anatolia[29] did not provide specific subclades for haplogroup E1b1b, a validated haplogroup prediction tool was used for determining those[16,17]. Y-haplogroup frequencies for Cypriots and for all other relevant populations can be found in S6 Table and S7 Table, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The other populations that were also covered in the same article demonstrate only minor differences in few percentages which typing. Petrejčíková et al (2014) used 3 different predictors for the research based on 12 STRs and obtained 98.80%, 97.59% and 98.19% accuracy for Whit Athey´s haplogroup predictor, Jim Cul-len´s haplogroup predictor and Vadim Urasin´s haplogroup predictor, respectively. Furthermore, Dogan et al (2016) used 4 haplogroup predictors for analysing the B&H population and obtained a 99% average accuracy while the current study obtained a 91% average accuracy for all populations.…”
Section: Discussionmentioning
confidence: 99%
“…Y chromosomal haplogroups can be assigned from Y-STR haplotypes using haplogroup predictors, which are very useful for analysing previous published Y-STR datasets (Dogan et al 2016;Dogan et al 2017;Heraclides et al 2017;Gurkan et al 2017) as well as validation purposes of haplogroup assignments based on Y SNP data (Petrejčíková et al 2014 andEmmerova et al 2017). The four haplogroup predictors that are in focus in this study are: Whit Athey haplogroup predictor (Athey 2006), Nevgen haplogroup predictor (Ćetković -Gentula and Nevski 2015), Vadim Urasin's…”
Section: Introductionmentioning
confidence: 99%